Perspectives of physicians on risk factors for patient aggression and violence against physicians in Chinese hospitals: a Q-methodology study - Yuhan Wu; Kees Ahaus; Jiaming Shi; Dahai Zhao; Martina Buljac-Samardzic (Human Resources for Health)
Abstract Background The prevalence of patient (and their relatives/friends) aggression and violence against healthcare professionals in general, and physicians in particular, is a recognized problem worldwide. While numerous risk factors for such aggression and violence from patients (and their relatives/friends) have been identified, little is known about which risk factors are perceived as relatively most important in a specific context and among a particular group, and about the potentially differing views on the relative importance. This lack of insight prohibits preventive measures being tailored to address the main risk factors. Method We conducted a Q-methodology study to investigate physicians’ perspectives on risk factors for aggression and violence from patients (and their relatives/friends) against physicians in Chinese hospitals. A total of 33 physicians from public Chinese hospitals participated in this study and were asked to rank 30 risk factors according to their importance in triggering violent incidents. In addition, respondents were asked to explain their ranking of most and least important risk factors. Results By employing a by-person factor analysis, four distinct perspectives on the importance of risk factors were identified: (1) unmet expectations of treatment and lack of resources; (2) perpetrator’s educational background and personal characteristics; (3) distrust and limited protection measures; and (4) perpetrator’s emotional well-being and poor interaction. There was a consensus across perspectives that failure to meet perpetrator’s expectations is one of the most important risk factors and that physician’s gender is one of the least important risk factors in the occurrence of patient (and their relatives/friends) aggression and violence against physicians in Chinese hospitals. Conclusions This study has identified four distinct perspectives held among physicians on the risk factors for patient aggression and violence against physicians in Chinese hospitals. These insights enable the development and prioritization of targeted measures to address specific risk factors according to the dominant views among physicians.